[PP.26.27] DIAGNOSTIC ROLE OF HOME BLOOD PRESSURE MONITORING IN PRIMARY CARE. (September 2017) - Ardeleanu, E.; Dorobantu, M.; Lighezan, D.; Lighezan, R.; Darabont, R.; Gurgus, D.; Tilea, I.; Domide, C.; Deleanu, A.; Varga, A.; Zorila, C.; Csuros, S.; et al.
Abstract : Objective: The aim of the study was the evaluation of the characteristics and advantages of home blood pressure monitoring (HBPM), compared with office blood pressure (BP) measurement and to establish its utility in primary care offices. Design and method: From 2314 annual examinations (1st. visit), office blood pressure (BP) measurement detected 255 subjects (11.01%) with newly diagnosed HT. On the second visit, involving 200 of these cases with grade I and II hypertension, office BP measurement detected hypertension in 182 (91%) patients and normal BP in 18 cases (9%). Home blood pressure monitoring confirmed in 128 of these cases (84.76%) sustained hypertension and in 23 (15.24%) white-coat hypertension (WCHT). Results: Average office BP in sustained hypertension was for systolic BP (SBP) 159.97 mmHg, SD ± 10.13, 95% CI 1.84 (158.13–161.81 mmHg) and average diastolic BP(DBP) was 94.59 mmHg, SD ± 5.62, 95% CI 1.03 (93.56–95.62 mmHg). In WCHT the average office SBP was 160.85, SD ± 6.31, 95% CI 2.46 (158.39–163.31 mmHg) and the average DBP was 96.61, SD ± 4.55, 95% CI 1.78 (94.83–98.39 mmHg). The average home BP for SBP in sustained hypertension group was 143.27 mmHg, SD ± 7.20, 95% CI 1.31 (141.96–144.58 mm Hg) and the average DBP was 86.83 mmHg (SD ± 4.97), 95% CI 0.90 (85.91–87.75 mmHg). In white-coat hypertension the home BP values were normal: SBP was 129.91 mmHg, SD ± 5.80, 95% CI 2.27 (127.63–132.19 mmHg) and DBP was 79.42 mmHg, SD ± 4.81, 95% CI 1.89 (77.53–81.31 ± mmHg). Conclusions: Home BP monitoring in primary care offices enables a quick, inexpensive and accurate diagnosis of sustained and of white-coat hypertension. It is superior to office BP measurement in evaluating the BP profile. In the absence of ABPM, home BP monitoring is the best recommended method for diagnosing white-coat hypertensio n. A more widely use in family medicine practice is therefore strongly recommended.